Modulatory-antibiotic activity of the essential oil from Eucalyptus citriodora against MDR bacterial strains - Pinheiro, Raizza Eveline E.; Chaves, Thiago P.; Melo, Eveny S.; Ali, Sultan; Ali, Shinawar Waseem; Umer, Muhammad; Gama, Gil Sander P.; Lira, Dalliane N. S.; Souza, Joào Sammy N.; Soares, Maria José dos S.; Santos, André de Souza; Mota, Rinaldo Aparecido; et al. (Cellular and Molecular Biology, 2020)
The growing number of bacterial strains resistant to therapeutic agents has been surpassing the various antibiotics developed by the chemical and pharmaceutical industries. This problem has driven the development of research using agents with antimicrobial potential, with an emphasis on plant-derived natural products. This study evaluated the chemical compounds present in Eucalyptus citriodora essential oil (EOEc) cultivated in northeastern Brazil and its properties as an antibacterial agent and resistance modifier against methicillin-resistant Staphylococcus aureus (MRSA) and Î²-lactamase-producing strains. The EOEc was obtained using the hydrodistillation method, later analyzed by GC/MS, presenting a total of twelve compounds, with citronellal (65.45%); citronellol (14.87%); isopulegol (11.80%) and citronellyl acetate (2.51%) as its main constituents. The microdilution test was used to determine the minimum inhibitory concentration (MIC) and the bacterial resistance modulation of the essential oil. The EOEc did not present significant activity against the tested strains (MIC > 1000 µg mL-1). However, when evaluating the capacity of the EOEc to modify the resistance of S. aureus and E. coli strains to different antimicrobials, synergistic effects were obtained with reduced MIC values for all tested antibiotics being obtained. The EOEc showed antimicrobial and Î²-lactam optimizing potential against resistant strains, presenting itself as a possible alternative for the use of these drugs at concentrations lower than those indicated against resistant strains.